Speed control for multi-three phase synchronous electrical motors in fault condition - Galassini, Alessandro; Costabeber, Alessando; Gerada, C. (2017)
The growth of electrification transportation systems is an opportunity for delving into new feasible solutions for more reliable and fault tolerant arrangements. So far, many investigations distant from the market have been carried out. Most of the works are looking at new control strategies adding extra components increasing manufacturing efforts and costs. Considering a nine phase synchronous multi-three phase electrical motor with disconnected neutral points, this manuscript compares the common speed reference configuration (where all the drives are configured in speed mode) and the torque follower configuration (where one drive is in speed mode and all the others are in torque mode). Furthermore, a post-fault operation in open-circuit condition is proposed. Analytical equations and experimental validation in nominal and fault condition are given by means of Matlab/Simulink simulations and by experimental on a 22kW test rig.